Analysis of Trends in Cosmetics Supervision Cases in Indonesia in 2021-2024 - Mohamad Kashuri; Taruna Ikrar; Gunawan Indrayanto (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
This study offers a comprehensive analysis of cosmetic product regulation in Indonesia from 2021 to 2024, examining enforcement trends, patterns of regulatory non-compliance, and the evolving oversight role of the Indonesian Food and Drug Authority (BPOM). Data were obtained from BPOM’s annual inspection and enforcement reports and analyzed descriptively to identify changes in regulatory compliance over time. The results reveal that the majority of violations originated from Small and Medium-Sized Enterprises (SMEs), accounting for 1–2% of total cases, while larger industries reported slightly higher rates (2.7–6.9%). A significant 165% surge in products without distribution permits was recorded from 2021 to 2022, followed by substantial reductions in 2023 (85%) and 2024 (32%). Adherence to Good Cosmetic Manufacturing Practices (GCMP) showed a consistent improvement from 2022 onwards. Violations involving labeling, advertising, and product claims also declined, though more than 1,500 cases are still reported annually. Public education campaigns have played a crucial role in enhancing consumer awareness and minimizing exposure to unsafe products. Enforcement data further demonstrate a reduction in formal sanctions and warnings, reflecting BPOM’s strategic pivot toward a more preventive and facilitative regulatory approach. Looking ahead, BPOM needs to strengthen industry compliance by expanding its technical assistance initiatives through both direct consultations and digital platforms, supporting a more risk-based and innovation-friendly regulatory environment.